2004
DOI: 10.1002/jnr.20087
|View full text |Cite
|
Sign up to set email alerts
|

Administration of N‐acetylcysteine after focal cerebral ischemia protects brain and reduces inflammation in a rat model of experimental stroke

Abstract: Free radicals and inflammatory mediators are involved in transient focal cerebral ischemia (FCI). Preadministration of N-acetylcysteine (NAC) has been found to attenuate the cerebral ischemia-reperfusion injury in a rat model of experimental stroke. This study was undertaken to investigate the neuroprotective potential of NAC administered after ischemic events in experimental stroke. FCI was induced for 30 min by occluding the middle cerebral artery (MCA). NAC (150 mg/kg) was administered intraperitoneally at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
132
0
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 216 publications
(150 citation statements)
references
References 56 publications
(58 reference statements)
9
132
0
8
Order By: Relevance
“…NAC is probably one of the most widely investigated agents that serves as a precursor of glutathione and has both antioxidant and anti-inflammatory properties. NAC has been shown to attenuate inflammation in various disease models such as ischemia-reperfusion injury in brain (Sekhon et al, 2003;Khan et al, 2004), lethal endotoxemia (Victor et al, 2003), animal model of multiple sclerosis (Lehmann et al, 1994;Stanislaus et al, 2005), and hypoxic-ischemic brain injury in neonatal brains (Jatana et al, 2006;Wang et al, 2007). In addition, we and others have reported the attenuation of brain white matter injury by NAC in the systemic maternal infection model of PVL (Cai et al, 2000;).…”
Section: Introductionmentioning
confidence: 70%
“…NAC is probably one of the most widely investigated agents that serves as a precursor of glutathione and has both antioxidant and anti-inflammatory properties. NAC has been shown to attenuate inflammation in various disease models such as ischemia-reperfusion injury in brain (Sekhon et al, 2003;Khan et al, 2004), lethal endotoxemia (Victor et al, 2003), animal model of multiple sclerosis (Lehmann et al, 1994;Stanislaus et al, 2005), and hypoxic-ischemic brain injury in neonatal brains (Jatana et al, 2006;Wang et al, 2007). In addition, we and others have reported the attenuation of brain white matter injury by NAC in the systemic maternal infection model of PVL (Cai et al, 2000;).…”
Section: Introductionmentioning
confidence: 70%
“…Furthermore, the treatment with GSNO in vitro inhibited the cytokine and/or LPS-induced iNOS expression and cytokine and/or LPS-mediated NF-kB luciferase activity both in rat primary astrocytes and BV2 cells (Figures 7 and 8), indicating that GSNO is an antiinflammatory agent. Inflammatory components in stroke may be amenable to treatment by antiinflammatory agents (Barone and Feuerstein, 1999) including Nacetylcysteine (Khan et al, 2004;Sekhon et al, 2003). Cerebral ischemia promotes activation of glial cells (resident microglia and astrocytes) and infiltration of blood-borne cells including monocytes (del Zoppo et al, 2000;Garcia et al, 1994;Stoll et al, 1998), leading to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that NAC protected against free oxygen radical injury, apoptosis, and inflammation. 24 However, Thomale et al found that after brain contusion, NAC was not effective at reducing the area of injury and did not influence post-traumatic brain edema formation. 25 Cakir et al investigated the effect of NAC on spinal cord ischemia-reperfusion injury in rabbits.…”
Section: Discussionmentioning
confidence: 99%